Нюша, Павлуша и Я: рассказы / Нина Ермолаева - Ермолаева Нина Георгиевна (Для семейного чтения, 2016)
Экземпляры: Ф. 1 (20200630) / Инвентарный номер: 46178 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: Е 74 / ГРНТИ: 17.82.10 / ББК: 84(2)